2009
DOI: 10.1007/s00038-009-5413-9
|View full text |Cite
|
Sign up to set email alerts
|

A cross-national profile of bullying and victimization among adolescents in 40 countries

Abstract: Objectives-(1) To compare the prevalence of bullying and victimization among boys and girls and by age in 40 countries. (2) In 6 countries, to compare rates of direct physical, direct verbal, and indirect bullying by gender, age, and country.Methods-Cross-sectional self-report surveys including items on bullying and being bullied were obtained from nationally representative samples of 11, 13 and 15 year old school children in 40 countries, N = 202,056. Six countries (N = 29,127 students) included questions abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

71
650
13
81

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 903 publications
(843 citation statements)
references
References 19 publications
71
650
13
81
Order By: Relevance
“…In an international comparison, Sweden has low rates of bullying (Chester et al, 2015;Craig et al, 2009), and the large-scale data made the analyses possible. However, the study also has some limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an international comparison, Sweden has low rates of bullying (Chester et al, 2015;Craig et al, 2009), and the large-scale data made the analyses possible. However, the study also has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies report that boys bully more than girls do (e.g., Craig et al, 2009;Nansel et al, 2001;Olweus, 1991;Stassen Berger, 2007;Wolke, Woods, Stanford, & Schulz, 2001), whereas the gender pattern in victimization is less definite (e.g., Craig et al, 2009;Due et al, 2005;Nansel et al, 2001). According to Olweus (1991), boys are more likely to be victims of direct bullying than girls, while the proportions of boys and girls who are exposed to indirect bullying are rather similar.…”
Section: Individual-level Characteristics Associated With Exposure Tomentioning
confidence: 99%
See 1 more Smart Citation
“…In Norway girls outperform boys in all subject, except from physical education (Bakken et al, 2008). In the case of bullying, there is a general tendency for boys to be more involved both as bullies and victims at all ages (Wendelborg et al, 2014, Seals and Young, 2003, Erdur-Baker, 2010, Salmivalli and Nieminen, 2002However, some researchers have found that girls are more involved in indirect or social bullying (Lagerspetz et al, 1988, Björkqvist et al, 1992, but this findings is not consistent (Craig et al, 2009). In the case of cyberbullying, no clear effect of either gender og age is found, although some findings suggest that that girls are more at risk of being targeted (Tokunaga, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Bullying e uso de substâncias psicoativas são temas recorrentes na literatura científica nacional e internacional, apontados como importantes problemas de saúde, que podem comprometer o desenvolvimento de todos os envolvidos [1][2][3][4][5] . A sua alta prevalência entre adolescentes, somada aos prejuízos associados à sua ocorrência, leva-os a serem considerados como sérios problemas de saúde pública 6 .…”
Section: Introductionunclassified